(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
“The basic purpose ofdevelopment is to enlarge people’s choices. In principle, these choices can beinfinite and can change over time. People often value achievements that do notshow up at all, or not immediately, in income or growth figures: greater accessto knowledge, better nutrition and health services, more secure livelihoods,security against crime and physical violence, satisfying leisure hours, politicaland cultural freedoms and sense of participation in community activities. Theobjective of development is to create an enabling environment for people toenjoy long, healthy and creative lives”, is how renowned economist Dr. MahbubulHaq defined Human resources Development (HD).